Faktor yang Mempengaruhi Pembelajaran Daring Melalui LMS pada Masa Covid 19 - Rasyid Ridho Hamidy; Mashur Mashur; Lalu Nurul Yaqin (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Online (e-learning) during the Covid-19 pandemic has become a trend in education that causes significant changes in learning, forcing universities to adapt to learning conditions during Covid 19. The purpose of this study was to determine the factors that influence online learning through the use of the Learning Management System (LMS) during the Covid 19 pandemic at Universitas Gunung Rinjani. Differences in LMS use based on some demographic information such as gender, location (place of residence), and age are also discussed to gain an in-depth understanding of the use of LMS during online learning. There are two research methods used in this study, namely quantitative and qualitative. The data collection process was carried out through an online survey instrument distributed to 6 Faculties 7 Study Programs at Universitas Gunung Rinjani. In addition, interviews with students will be conducted to gain an in-depth understanding of LMS use in their learning. The findings of this study indicate that LMS use during Covid 19 learning can run well; this can be seen from the participants' perceptions of usefulness, ease of use, subjective norms and attitudes of self-efficacy and support from lecturers and colleagues.